Do darweshson ka qisa - Nazar Sabir (Ferozesons; Pakistan, 2012)
Do Darweshon Ka Qisa is a timeless story of two mystics whose wisdom and encounters teach valuable lessons about humility, kindness, and the search for spiritual truth.